2008
DOI: 10.4314/mmj.v20i2.10958
|View full text |Cite
|
Sign up to set email alerts
|

Why do people refuse to take part in biomedical research studies? Evidence from a resource-poor area

Abstract: Participants' refusal to take part in research is an unpleasant experience that investigators face.. This paper highlights some of the reasons why people from resource-poor settings refuse to take part in health research. This paper also highlights standards which investigators can adopt to avoid unnecessary refusals and at the same time ensure that individuals have the right to participate and freedom to refuse. Our objective was to explore reasons why people refuse to join research studies. We conducted focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…The issues around consent can be very broad depending on what the issue is that someone needs to give consent to and the process of obtaining consent can further be influenced by various factors including culture, norms, values, traditions, beliefs and practices . In the Zambian context, for example, when one consents to getting married, it often involves more than just the two intending to get married.…”
Section: Introductionmentioning
confidence: 99%
“…The issues around consent can be very broad depending on what the issue is that someone needs to give consent to and the process of obtaining consent can further be influenced by various factors including culture, norms, values, traditions, beliefs and practices . In the Zambian context, for example, when one consents to getting married, it often involves more than just the two intending to get married.…”
Section: Introductionmentioning
confidence: 99%
“…Topics examined include comprehension of study information and factors affecting comprehension (Bhansali et al, 2009; Kaewpoonsri et al, 2006; Kass, Maman, & Atkinson, 2005; Krosin et al, 2006; Manafa, Lindegger, & Ijsselmuiden, 2007; Marshall, 2006; Mathews et al, 2005; Minnies et al, 2008; Moodley, Pather, & Myer, 2005; Oduro et al, 2008; Pace, Emanuel et al, 2005; Pace, Talisuna et al, 2005), effects of interventions to improve comprehension (Joseph et al, 2006; Penn & Evans, 2010; Sarkar et al, 2010; Vallely et al, 2010), means of evaluating comprehension (Lindegger et al, 2006; S. Molyneux et al, 2007), voluntariness of participation and factors affecting voluntariness (Kass et al, 2005; Marshall, 2006; Nalugoda et al, 2009; Pace, Emanuel et al, 2005; Pace, Talisuna et al, 2005; Woodsong & Karim, 2005), motivations for consenting or declining to take part in research (Kass et al, 2005; Masiye et al, 2008; Mfutso-Bengo, Masiye et al, 2008; Mfutso-Bengo, Ndebele et al, 2008; Mtunthama et al, 2008; Nabulsi, Khalil, & Makhoul, 2010), decision-making processes and the involvement of others in such processes (Masiye et al, 2008; C. S. Molyneux et al, 2005; Tindana, Kass, & Akweongo, 2006; Woodsong & Karim, 2005), participants’ and communities’ understandings and views of research (Fairhead, Leach, & Small, 2006a, 2006b; Geissler et al, 2008; Gikonyo et al, 2008; Hill et al, 2008; C.…”
mentioning
confidence: 99%
“…Discussions about the acceptability of research to invited participants often lack explicit definitions (Feeley et al, 2009). Some analyses equate acceptance with participation, contrasting this with refusal to participate, as in "deciding whether to accept or decline the research" (Mfutso-Bengo et al, 2008, p.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to what people find acceptable, several benefits and disadvantages perceived by invited participants for this vaccine trial are reported for other research, including appreciation of access to health care or material compensation, and concerns around blood samples (Fisher et al, 2011;Mfutso-Bengo et al, 2008, 2015Masiye et al, 2008). Those invited to enrol weigh up these perceived benefits and risks (Fairhead et al, 2004;Fisher et al, 2011).…”
mentioning
confidence: 99%